2008
DOI: 10.1002/jca.20173
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Cobe AutoPBSC and Gambro Elutra as a platform for monocyte enrichment in dendritic cell (DC) therapy: Clinical study

Abstract: Monocytes are a common source for generating dendritic cells (DCs). The aim of the present study was to evaluate the efficiency of a platform for monocyte collection and enrichment in a clinical setting. The platform was based on the combination of two semiautomated devices; the Cobe Spectra Auto PBSC for mononuclear cells (MNC) collection followed by counterflow elutriation for monocyte enrichment (Gambro BCT Elutra). Twenty-four patients with various types of epithelial cancer participated in the study. MNC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…However, almost all neutrophils were also found in fraction 5 with monocytes and almost all RBCs were in fractions 1 and 2 with lymphocytes. These results are similar to those of other reports which evaluated the same instrument to isolate monocytes from small numbers of PBMC concentrates collected from healthy subjects [7,9,11,2023], pooled whole blood buffy coat products [8,24] and PBMCs from up to 24 patients with cancer [10,11,16]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, almost all neutrophils were also found in fraction 5 with monocytes and almost all RBCs were in fractions 1 and 2 with lymphocytes. These results are similar to those of other reports which evaluated the same instrument to isolate monocytes from small numbers of PBMC concentrates collected from healthy subjects [7,9,11,2023], pooled whole blood buffy coat products [8,24] and PBMCs from up to 24 patients with cancer [10,11,16]. …”
Section: Discussionsupporting
confidence: 90%
“…We found that only about one-third of the products met these criteria, but the quantity of neutrophils among the monocytes could be reduced greatly by density gradient separation with little loss of monocytes. We investigated factors that might influence the neutrophil content of the elutriated monocytes and found that the portion of neutrophils in the monocyte rich fraction 5 was dependent on the quantity of neutrophils loaded into elutriator at the onset of the process; this result is similar to the findings of Chen et al [10]. While we elected to deplete neutrophils from some elutriated monocytes, others have reported that the presence of as much as 20% to 30% neutrophils in elutriated monocytes used to manufacture DCs does not affect the quality of the final mature DC product [24].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Elutriated monocytes were obtained from healthy adult donors, after signing informed consent forms, from the Department of Transfusion Medicine at the National Institutes of Health using the Gambro Elutra method [30]. The preparation, in general, contained over 85% monocytes, <10% neutrophils, and <5% lymphocytes.…”
Section: Methodsmentioning
confidence: 99%